Effective Therapy of Insulinoma by Using Long-Acting Somatostatin Analogue. A Case Report and Literature Review - Jawiarczyk, A.; Bolanowski, M.; Syrycka, J.; Bednarek-Tupikowska, G.; Kałużny, M.; Kołodziejczyk, A.; Domosławski, P. (Experimental and Clinical Endocrinology & Diabetes, 2012)
We are reporting a case of 68-year-old woman with insulinoma, after a non-successful tumor surgery and a long-term diazoxide treatment. She had a lot of hypoglycemia cases, and a weight gain of 50 kg. An abdominal CT scan demonstrated a tumor 28 mm in the diameter, in the head of the pancreas. The patient did not agree for the repeated insulinoma surgery. Furthermore, we found a lesion in the left adrenal gland (14 mm in the diameter) and in the right lung (8 mm in the diameter). Pheochromocytoma was diagnosed on the basis of hypertension, elevated levels of normetanephrine in the 24-h urine collection, and an elevated level of norepinephrine in a plasma sample. After the left adrenal gland removal we observed lower blood pressure. Since we had revealed the presence of somatostatin receptors by the somatostatin receptors scintigraphy, we decided to control hypoglycemia by a monthly subcutaneous administration of the long-acting lanreotide. Because of higher glucose levels (300–400 mg/dl) we started an intense insulin therapy. Nowadays, the patient feels better, she has lost 20 kg of her body weight, and we have observed normal blood glucose levels during the long-term lanreotide treatment. We have noticed neither side effects nor hypoglycemic episodes and we have reduced the dose of insulin. The presented case can be an evidence of the effective treatment of the pancreatic neuroendocrine tumor of insulinoma type, with somatostatin analogue.
Keywords: insulinoma; lanreotide; diabetes mellitus